A systematic evaluation of various methods for quantifying food protein hydrolysate peptides. (1st January 2019) - Nwachukwu, Ifeanyi D.; Aluko, Rotimi E.
Highlights: Plant and animal protein enzymatic hydrolysates were evaluated for protein content. Protein was determined using Kjeldahl, Dumas, colorimetric and far-UV methods. Amino acid analysis was also used for protein determination. Lowry, Dumas and amino acid analysis were the most positively correlated. Abstract: This work was carried out to identify accurate methods that could be recommended for the quantification of proteins in food protein hydrolysates. Following hydrolysis with 4% alcalase, the amount of protein in various hydrolysate samples was measured using seven different analytical methods. Although the data obtained using different methods varied, HPLC amino acid analysis with a Pico-Tag column indicated that the highest concentration of amino acids in the protein hydrolysates was present in the casein sample while the lowest amount of protein was found in the sample of hempseed studied. However, the amino acid analysis data was mostly positively correlated with the Dumas and Lowry methods. We conclude that where available, amino acid analysis provides the best estimate of protein content of hydrolysates but the Dumas and Lowry methods can also be recommended as alternatives.